Clinical implication of HLA class I expression in breast cancer - Kaneko, Koichi; Ishigami, Sumiya; Kijima, Yuko; Funasako, Yawara; Hirata, Munetsugu; Okumura, Hiroshi; Shinchi, Hiroyuki; Koriyama, Chihaya; Ueno, Shinichi; Yoshinaka, Heiji; Natsugoe, Shoji (BMC cancer, 2011)
Background Human leukocyte antigen (HLA)-class I molecules on tumor cells have been regarded as crucial sites where cytotoxic T lymphocytes (CTL) can recognize tumor-specific antigens and are strongly associated with anti-tumor activity. However, the clinical impact of HLA class I expression in breast cancer has not been clarified. Methods A total of 212 breast cancer patients who received curative surgery from 1993 to 2003 were enrolled in the current study. HLA class I expression was examined immunohistochemically using an anti-HLA class I monoclonal antibody. The correlation between HLA class I positivity and clinical factors was analyzed. Results The downregulation of HLA class I expression in breast cancer was observed in 69 patients (32.5%). HLA class I downregulation was significantly associated with nodal involvement (p < 0.05), TNM stage (p < 0.05), lymphatic invasion (p < 0.01), and venous invasion (p < 0.05). Patients with preserved HLA class I had significantly better disease-free interval (DFI) than those with loss of HLA class I (p < 0.05). However, in multivariable analysis, HLA class I was not selected as one of the independent prognostic factors of disease-free interval. Conclusion The examination of HLA class I expression is useful for the prediction of tumor progression and recurrent risk of breast cancer via the antitumor immune system.